Biological and technical challenges for implementation of yeast‐based biosensors - Wahid, Ehtisham; Ocheja, Ohiemi Benjamin; Marsili, Enrico; Guaragnella, Cataldo; Guaragnella, Nicoletta (Microbial biotechnology, 2023)
Biosensors are low‐cost and low‐maintenance alternatives to conventional analytical techniques for biomedical, industrial and environmental applications. Biosensors based on whole microorganisms can be genetically engineered to attain high sensitivity and specificity for the detection of selected analytes. While bacteria‐based biosensors have been extensively reported, there is a recent interest in yeast‐based biosensors, combining the microbial with the eukaryotic advantages, including possession of specific receptors, stability and high robustness. Here, we describe recently reported yeast‐based biosensors highlighting their biological and technical features together with their status of development, that is, laboratory or prototype. Notably, most yeast‐based biosensors are still in the early developmental stage, with only a few prototypes tested for real applications. Open challenges, including systematic use of advanced molecular and biotechnological tools, bioprospecting, and implementation of yeast‐based biosensors in electrochemical setup, are discussed to find possible solutions for overcoming bottlenecks and promote real‐world application of yeast‐based biosensors. Yeast‐based biosensors combine the microbial with the eukaryotic advantages, including possession of specific receptors, stability and high robustness. Most yeast‐based biosensors are still in the early developmental stage, with only a few prototypes tested for real applications. Biological, molecular and technical issues are discussed to find possible solutions for overcoming bottlenecks and promote real‐world application of yeast‐based biosensors.